Inflammation and apoptosis induced by mastoparan Polybia-MPII on skeletal muscle - Rocha, Thalita; Soares de Barros, Luciano Libardi; Fontana, Karina; de Souza, Bibiana Monson [UNESP]; Palma, Mario Sergio [UNESP]; da Cruz-Hoefling, Maria Alice (Pergamon-Elsevier B.V. Ltd, 2010)
Mastoparan firstly described as an inducer of mast cell granules exocytosis has been also related to many essential mechanisms of cell function. In skeletal muscle tissue the best characterization of mastoparan effect was induction of myonecrosis. We examined the ability of mastoparan Polybia-MPII from Polybia paulista wasp venom to induce apoptosis and inflammation in mouse tibial anterior muscle. The activation of caspase 3 and 9, the expression of INF-alpha, IFN-gamma, CD68 and CD163 proteins, specific of resident and migrant macrophages, respectively, were examined (3 h to 21 d). TUNEL-positive nuclei were found both in damaged and normal-looking muscle fibres, whereas the caspases, cytokines and macrophages proteins were only in damaged fibres. The caspase 3 and 9 expression and the immunolabelled areas of TNF-alpha and IFN-gamma were significantly higher compared to control. TUNEL-positive nuclei and TNF-alpha expression were also present in regenerating fibres. CD68 and CD163 signalize necrotic debris removal, release of chemo-attractants and cytokines which have been considered a pre-requisite for muscle regeneration. High levels of cytokines coincided with the intense muscle proteolysis by mastoparan (3-24 h) and the climax of regeneration (3 d) whereas cytokines decline corresponded to periods of tissue remodeling and intense fibre protein synthesis (7-21 d). We conclude that the mastoparan Polybia-mPII causes myonecrosis and apoptosis, the latter probably involving caspases signalling, corroborated by mitochondrial damage, and cytokines activation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Caspase; Cytokines; Macrophage; Myonecrosis; Skeletal muscle; TUNEL reaction